Memorized Discrete Systems and Time-delay - Luo, Albert C. J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book examines discrete dynamical systems with memory-nonlinear systems that exist extensively in biological organisms and financial and economic organizations, and time-delay systems that can be discretized into the memorized, discrete dynamical systems. It book further discusses stability and bifurcations of time-delay dynamical systems that can be investigated through memorized dynamical systems as well as bifurcations of memorized nonlinear dynamical systems, discretization methods of time-delay systems, and periodic motions to chaos in nonlinear time-delay systems. The book helps readers find analytical solutions of MDS, change traditional perturbation analysis in time-delay systems, detect motion complexity and singularity in MDS; and determine stability, bifurcation, and chaos in any time-delay system.
Memorized Linear Discrete Systems -- Memorized Nonlinear Discrete Systems -- Discretization of Time-delay Systems -- Periodic Flows in Time-delay Systems -- Time-delay Duffing Oscillator.
Keywords: Dynamics; Nonlinear theories; Nonlinear Optics; System theory; Bioinformatics; Econometrics; Applied Dynamical Systems; Nonlinear Optics; Complex Systems; Computational and Systems Biology; Econometrics